Annual World Bank Conference on Development Economics, 1995 - Bank Conference on Development Economics Washington, D.C. 1995; Bruno, Michael; Pleskovic, Boris; World Bank. (Washington, DC: World Bank, 1996)
"The Annual World Bank Conference on Development Economics provides a forum for debate and the exchange of ideas and information between World Bank staff and development researchers and practitioners from around the world. The 1995 conference addresses four themes: (1) where we stand on inequality, poverty, and growth; (2) demographic change and development; (3) aid and development; and (4) fiscal decentralization."
Annual World Bank Conference on Development Economics 1995 -- CONTENTS -- INTRODUCTION -- References -- Opening Remarks: The "How" of Development -- Keynote Address: Argentina's Miracle? From Hyperinflation to Sustained Growth -- Productivity Growth and Economic Reform -- The Inflation Stabilization Program -- The Social Costs of Reforms -- Conclusion -- Note -- References -- In Memoriam: A Tribute to Hollis Chenery -- Inequality, Poverty, and Growth: Where Do We Stand? -- Comment on "Inequality, Poverty, and Growth: Where Do We Stand?" by Albert Fishlow -- Comment on "Inequality, Poverty, and Growth: Where Do We Stand?" by Albert Fishlow -- Comment on "Inequality, Poverty, and Growth: Where Do We Stand?" by Albert Fishlow -- Floor Discussion of "Inequality, Poverty, and Growth: Where Do We Stand?" by Albert Fishlow -- Research on Poverty and Development Twenty Years after Redistribution with Growth -- Comment on "Research on Poverty and Development Twenty Years after [[i]]Redistribution with Growth[[/i]]," by Pranab Bardhan -- Floor Discussion of "Research on Poverty and Development Twenty Years after [[i]]Redistribution with Growth[[/i]]," by Pranab Bardhan -- Government Provision and Regulation of Economic Support in Old Age -- Comment on "Government Provision and Regulation of Economic Support in Old Age," by Peter Diamond -- Message 1: There Is No Holy Grail -- Message 2: Effective Government is Critical -- Message 3: Policy Design Depends on the Starting Point -- Message 4: The Key Variable Is Output -- Notes -- Reference -- Comment on "Government Provision and Regulation of Economic Support in Old Age," by Peter Diamond -- Comment on "Government Provision and Regulation of Economic Support in Old Age," by Peter Diamond -- Floor Discussion of ''Government Provision and Regulation of Economic Support in Old Age," by Peter Diamond -- Engendering Economics: New Perspectives on Women, Work, and Demographic Change -- Comment on "Engendering Economics: New Perspectives on Women, Work, and Demographic Change," by Nancy Folbre -- Comment on "Engendering Economics: New Perspectives on Women, Work, and Demographic Change," by Nancy Folbre -- Floor Discussion of "Engendering Economics: New Perspectives on Women, Work, and Economic Change," by Nancy Folbre -- Why is There Multilateral Lending? -- Comment on "Why is There Multilateral Lending?" by Dani Rodrik -- Comment on "Why is There Multilateral Lending?" by Dani Rodrik -- Floor Discussion of "Why Is There Multilateral Lending?" by Dani Rodrik -- Incentives, Rules of the Game, and Development -- Comment on "Incentives, Rules of the Game, and Development," by Elinor Ostrom -- Comment on "Incentives, Rules of the Game, and Development," by Elinor Ostrom -- Floor Discussion of "Incentives, Rules of the Game, and Development," by Elinor Ostrom -- Is Growth in Developing Countries Beneficial to Industrial Countries? -- Comment on "Is Growth in Industrial Countries Beneficial to Industrial Countries?" by Richard N. Cooper -- Comment on "Is Growth in Developing Countries Beneficial to Industrial Countries?" by Richard N. Cooper -- Floor Discussion of "Is Growth in Developing Countries Beneficial to Industrial Countries?" by Richard N. Cooper -- Fiscal Federalism and Decentralization: A Review of Some Efficiency and Macroeconomic Aspects -- Comment on "Fiscal Federalism and Decentralization: A Review of Some Efficiency and Macroeconomic Aspects," by Vito Tanzi -- Comment on "Fiscal Federalism and Decentralization: A Review of Some.
Includes bibliographical references.
Keywords: Paises subdesenvolvidos (economia); BUSINESS & ECONOMICS -- -- Urban & Regional; Electronic books; Development economics; Developing countries -- -- Economic policy; Developing countries -- -- Economic conditions; Electronic books